Comparison of Mo and ITO back contacts in CIGSe solar cells: Vanishing of the main capacitance step. (21st October 2021) - Schneider, Thomas; Dethloff, Christiane; Hölscher, Torsten; Kempa, Heiko; Scheer, Roland
Abstract: Admittance measurements of Cu (In, Ga)Se2 (CIGSe) solar cells typically show at least one capacitance step, the so‐called N1 signal. Its origin is still under debate, even though the signal is present in almost all CIGSe solar cells. In this work, CIGSe solar cells with different absorber layer thicknesses have been prepared on Mo and on indium tin oxide (ITO)‐based back contacts. The samples were analyzed by temperature‐dependent current–voltage (JV) and admittance measurements. No N1 signal was found for ITO‐based samples. The N1 signal was also absent in Mo‐based solar cells with an ultrathin absorber layer, unless a forward bias voltage was applied. The observations can be consistently explained by a back contact barrier, which is only present in the Mo‐based solar cells. The explanation is further supported by measured JV curves and by theoretical simulations. The results give a strong indication that the N1‐signal is due to a back contact barrier. While a back contact barrier is not necessarily detrimental for regular CIGSe solar cells, it may be an issue for CIGSe solar cells with ultrathin absorbers, where a so‐called punch‐through effect can occur. Abstract : Admittance measurements of CIGSe solar cells typically show at least one capacitance step, the so‐called N1 signal. However, we found no N1 signal in samples based on an ITO back contact. The observations can be consistently explained by a back contact barrier, which is only present in samples with a Mo back contact.